STUDENT’S RECEPTION OF NOVEL “NEGERI LIMA MENARA” FROM GENDER PERSPECTIVE - Rani Fairuz; I Wayan Dirgeyasa; Rahmad Husein (LINGUISTIK TERAPAN, 2018)
This research dealt with the students’ reception on the intellectual and emotional domain of novel which entitled “Negeri Lima Menara” from gender perspective. The objectives of this study were: (1) to investigate students’ reception of the novel at the intellectual aspect from gender perspective. (2) to investigate students reception of the novel at the emotional aspect from gender perspective. The data were obtained from questionnaire and the source of data were 32 students 16 male and 16 female from two classes students at second semester of language and arts faculty at state university of Medan, By applying purposive sampling. The research design of this study applied descriptive qualitative. The data were collected by administering questionnaire. The results of data analysis in general were (1) Male students were more good reception in both intellectual domain and emotional domain. Furthermore, the points of intellectual domain (respectively-%) were Structure 40.625%, Language 43.75%, Theme 50%, Tempo 15.625%, and the points of emotional domain (respectively-%) were Interest 43.75%, Authenticity 34.375%, the ability to belief 40.625% contained on the novel.However, female students’ was higher in 2 points both in intellectual domain and emotional domain. Furthermore, the two points of intellectual domain (respectively-%) were Characterization 50%, Plot 43.75% and the 2 points of emotional domain (respectively-%) Involvement 46.875%, Joy 43.75% contained on the novel. On the other hand both male and female have an equal point of emotional domain (respectively-%) they were Emotion 43.75%, but male had high score than female, male score 65 meanwhile female score 63 at the emotion point of emotional domain. Implication: male is more rationally meanwhile female is more emotionally. Keywords: students’ reception, intelectual, emotional domain, gender’s perspective.